Determining the Thickness of Peat Soil in Punggur Kecil Village Kubu Raya Regency Based on Resistivity Values - Annisa Putri; Zulfian Zulfian; Joko Sampurno (Departement of Physics Faculty of Mathematics and Natural Sciences, and Institute of Research and Community Services Udayana University, Kampus Bukit Jimbaran Badung Bali, 2025)
Information regarding peat thickness in Punggur Kecil Village, Kubu Raya Regency, West Kalimantan Province, is crucial for supporting various activities. Therefore, this study aimed to determine peat thickness in the village using the resistivity method with a Wenner configuration. Data was collected along four survey lines, each measuring 50 m. The results indicated that the resistivity values of the peat layer ranged from 95 to 282 Ωm. The thickness of the peat soil at the research location varies between 1 to 3.7 m, which can be classified as medium, deep, and very deep peat. These interpretation results align with the validation data from drilling. The layer beneath the peat was identified as clay, with resistivity values ranging from 0.138 to 32 Ωm. Based on these findings, the wooden pile method is the recommended land preparation method for constructing this area.